Fertility-sparing surgery in early-stage cervical cancer: laparoscopic versus abdominal radical trachelectomy - Zuoxi He; Ce Bian; Chuan Xie (BMC, 2022)
Abstract Background Radical trachelectomy is an acceptable alternative to radical hysterectomy for patients with early-stage cervical cancer who wish to preserve reproductive function. This study is designed to compare the laparoscopic versus abdominal radical trachelectomy and provide oncological and obstetric outcome data on patients who have undergone fertility-sparing surgery. Methods We retrospectively analyzed all early-stage cervical cancer patients who underwent abdominal radical trachelectomy (ART) or laparoscopic radical trachelectomy (LRT) between January 2005 and June 2017 in West China Second University Hospital, Sichuan University. Patients' clinical details and follow-up were obtained from hospital records. Results A total of 33 patients (5 with IA1, 2 with IA2, and 26 with 1B1) were included, including 18 patients treated with ART and 15 patients treated with LRT. The median age at initial diagnosis was 30.00 ± 4.30 years (range 22-39). The mean follow-up time was 74.67 months. Among the 33 patients, 2 patients (6.06%, 1 abdominal/1 laparoscopic) developed recurrence, and there are no evidence of disease for the remaining 31 patients till now. The overall survival rate 96.99% (32/33). The LRT group had a shorter hospital stay (P = 0.01) and less blood loss (P < 0.01) than the ART group. There is no significant difference in the length of operative time (P = 0.48) between the two surgical routes. Overall, 15/33 patients (45.45%) have tried to conceive. 6 (40.00%) patients were pregnant and 6 (40.00%) patients were infertility. The ART group had a higher clinical pregnancy rate (P = 0.03) than the LRT group. Conclusions There is no statistically significant difference in oncological outcome between the two surgical approaches. The clinical pregnancy rate in the ART group was significant higher than that in the LRT group. However, LRT resulted in less blood loss and decreased length of hospital stay.